Expanding Access To Justice Through E-Court In Indonesia - Santiadi, Kukuh (Universitas Islam Indonesia, 2019)
Indonesia's Supreme Court (MA) has started a new initiative by applying modern technology to the justice system through e-court. This new measure is a sign that the court responds the development in information technology while improving the quality of legal administration which has long been considered complicated by those seeking justice. This article raises a problem related to the implementation of the e-court system. This article uses a normative approach by obtaining data from various reports and books to be analyzed further and presented descriptively. It tries to explore whether the implementation of e-court has an impact on the efficiency of the administration of legal proceedings as well as an increase in transparency in the process of seeking justice and encouraging professional, transparent, accountable, effective and efficient justice administrationKeywords: Access to justice; e-court; modern courtMemperluas Akses Keadilan Melalui E-Court Di IndonesiaAbstrakMahkamah Agung (MA) Indonesia telah memulai inisiatif baru dengan menerapkan teknologi modern pada sistem peradilan melalui e-court. Langkah baru ini merupakan tanda bahwa pengadilan merespon perkembangan teknologi dan informasi sekaligus meningkatkan kualitas administrasi hukum yang selama ini dianggap rumit oleh pencari keadilan. Tulisan ini mengangkat permasalahan terkait penerapan sistem e-court. Tulisan ini menggunakan pendekatan normatif dengan memperoleh data dari berbagai laporan dan buku untuk dianalisis lebih lanjut dan disajikan secara deskriptif. Penelitian ini mencoba menelusuri apakah penerapan e-court berdampak pada efisiensi penyelenggaraan proses hukum serta peningkatan transparansi dalam proses mencari keadilan dan mendorong penyelenggaraan peradilan yang profesional, transparan, akuntabel, efektif dan efisien.Kata kunci: Akses ke Pengadilan; E-Court; Pengadilan Moderen